Impact of nutrient supplementation and physiological stress on male fertility. Systematic review - Arroyo Helguera, Omar; Nolasco Garduño, Vanessa Guadalupe; Sánchez Sánchez, Carolina; De León Ramírez, Yeimy (Horizonte Sanitario, 2025)
Objective: We are interested in the scientific evidence of the impact of nutrient supplementation and physiological stress on male fertility. Materials and methods: An analysis was carried out following the guidelines of the PRISMA guide in the databases of PubMed, Cochrane, and Redalyc, the keywords used were male infertility, physiological stress, nutrition, and fertility. or fertility. The search was carried out from December 2019 to January 2023. Results: The search engines used to conduct our search were PubMed, Redalyc, and Cochrane. These search engines, implementing the PRISMA declaration, yielded 664 articles. After excluding duplicates, the total was 312. We eliminated 100 articles associated with COVID-19. We also limited the search to those not related to any other pathology such as diabetes, hypertension, cancer, heart disease, etc., resulting in a total of 128 articles. Of these, 70 articles corresponding to systematic reviews were eliminated. Finally, the inclusion and exclusion criteria were applied, resulting in a total of 4 articles. Conclusions: Scientific evidence shows that poor nutrition is associated with increased stress levels, which can lead to infertility; however, the evidence for this remains limited because it is an understudied area. Keywords: Nutrients; Stress, Physiological; Infertility, Male.